Palestine in the Second World War : strategic plans and political dilemmas, the emergence of a new Middle East - Sharfman, Dafnah (Brighton ; Chicago : Sussex Academic Press, 2014)
While the conflicts and national aspirations in British mandatory Palestine in particular and the Middle East in general were evident before the outbreak of the Second World War, the war itself accelerated and enhanced national expectations and presented continuing tactical and strategic dilemmas to British, Arab, and Jewish leaders. British strategic policy during the war failed to provide answers to the political issues of the growing national demands in Palestine, and led to severe distrust of British policy among Arabs and Jews, as the two communities were framing mostly opposing reactions to wartime developments, and to conflicting expectations and policies toward postwar solutions for Palestine. The aim of this work is to analyze the continual development of strategic plans and political dilemmas that arose during the war period, which led to the subsequent postwar circumstance where American and Soviet involvement impacted on the strategic thinking of all involved parties, notwithstanding the British military victory. Analysis includes: the prewar British strategic situation in Palestine, and the war events in Palestine and its Middle East neighbor countries (at the military-strategic level and the repercussions of the outcome of the war for the local Palestinian population). At the heart of the discussion lies British interests and policies framed toward Jews and Arabs; analysis of the two communities' conflicting interests and policies; and the resultant sea-change in the establishment of the Jewish state which brought in its wake the emergence of a New Middle East.
Part I. The military campaigns of 1939-1942 -- part II. British-Jewish tension, 1943-1945.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: World War, 1939-1945 -- Palestine; Palestine -- History -- 1929-1948.; Zionism -- Palestine -- History -- 20th century; Arab nationalism -- Palestine -- History -- 20th century; Palestine -- Strategic aspects; Guerre mondiale, 1939-1945 -- Palestine; Palestine -- Histoire -- 1929-1948.; Nationalisme arabe -- Palestine -- Histoire -- 20e siècle.; HISTORY -- Middle East -- General; HISTORY -- Asia -- General; Arab nationalism; Zionism; Middle East -- Palestine; 1900-1999; History